La agresividad de los estudiantes del primer año de bachillerato, paralelos “A”, “B”, “C”, y su incidencia en el rendimiento académico, de la unidad educativa “Combatientes de Tapi” del cantón Riobamba, provincia de Chimborazo, en el periodo Quimestral marzo – julio 2015 - Ramos Caiza, Dario Javier (2016)
Aggression is a type of conduct oriented to cause pain to another person, Nowadays aggressiveness in our environment has increased in education. This problem has existed since our existence. Aggression was instrumented in reaction methods based on oppression and abuse towards another person; physical, psychological, verbal and sexual violence and intimidation, which is mainly devoted to attack or intimidate another student to reach a reaction from the assaulted. In this situation, adolescents have been directly affected as they opt to use of violence as a way to solve conflicts. The educational institution called “Combatientes de Tapi” located in Riobamba city has become one of the main scenarios in which the teenagers express their psychological emotional and aggressive behavior that can be very dangerous for the people involved, as well as for the aggressor and the victim who must be concerned from both school authorities and parents about the negative consequences that this type of behavior can causes of teaching and learning. This project pretends to contribute to identify the causes of the problem and its prevalence in the most common forms of aggression among students because it can cause serious issues such as; deficiency in their academic performance, school failure, lack of socialization and possible difficulties of adaptation during their social and personal lives.